Akuaponik sebagai Solusi untuk Produksi Pangan Halal yang Berkelanjutan di Lahan Terbatas - Hermialingga, Septi; Agustin , Venny; Wahyu Pamungkas, Ilham; Anggana Rarassari, Madyasta; Binti Maidin , Nur Hamizah; Lase, Ervina Natalia; Adhyanova, Nyimas Fifi Almeizi; Anfreli Eshan, Sarfaraz (Universitas Muhammadiyah Palembang, 2026)
Aquaponics is an innovative solution that integrates fish farming (aquaculture) and plant cultivation (hydroponics) through land and water efficiency to provide halal food at SMA Islam Al-Amalul Khair, Palembang. This community service activity aims to provide education and training on the implementation of vertical aquaponics as a sustainable food production model in a school environment. The program was implemented using a participatory approach, actively involving partners in every stage, including observation and planning, socialization, technology implementation, and evaluation. The results indicated that installing the units inside the classroom effectively enhanced learning quality, simplified operational monitoring, and minimized the risk of damage from external factors. Final evaluations through interviews and direct observations confirmed high enthusiasm and a significant increase in students' understanding of aquaponics concepts and halal food self-sufficiency. This program is expected to be a strategic step toward achieving independent food security and serving as a sustainable educational medium in an educational setting.